Pengaruh Kompetensi Dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pemerintah Desa Dalam Mengelola Alokasi Dana Desa: (Studi Kasus Pada Desa Kecamatan Tanah Pinem) - Sahala Purba; Rintan Saragih; Tika Meisiska Br Sembiring (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to examine and analyze the effect of competence and internal control system on village government accountability in managing village fund allocations and to test and analyze the effect of competence and internal control system jointly on village government accountability in managing village fund allocations. This type of research is quantitative research and uses primary data. The population in this study were village officials in Tanah Pinem District and the sample used the census method. The data collection method used was a questionnaire given to village officials in Tanah Pinem District, amounting to 48 people. The data analysis method used in this research is descriptive analysis and multiple linear regression. The results of this study indicate that competence has a positive but not significant effect on village government accountability, while partially the internal control system has a positive and significant effect on village government accountability. Simultaneously, competence and internal control system have a positive and significant effect on village government accountability.